EFFECT OF THE DEPOSITION SITE OF SEMINAL PLASMA ON THE OVULATION AND CORPUS LUTEUM DEVELOPMENT IN ALPACAS - Panez L., Susan (2009)
The present study was carried out to evaluate the effect of deposition site of seminal plasma on the ovulation rate and size of corpus luteum in alpacas. Non-lactating females bearing a ≥7 mm follicle detected by ultrasound were selected (n = 91). Follicular wave was synchronized by injecting 5 mg of LH and then, the presence of a dominant follicle ≥7 mm was determined 12 days later through ultrasound evaluation. Alpacas were assigned to one of six experimental groups: G1 (n=16) seminal plasma (SP) by intramuscular injection – i.m.; G2 (n=15) phosphate-buffered saline (PBS) i.m.; G3 (n=16) SP by intrauterine administration – i.u.; G4 (n=15) PBS i.u.; G5 (n=15) SP i.u. with curettage; G6 (14) PBS by i.u. with curettage. Ovulation rate and corpus luteum were determined by ultrasound evaluation on D2 and D8 (D0 = day of treatment). Serum samples were taken from the jugular vein on D0, D3 and D9 to determine progesterone profiles by radioimmunoassay. Ovulation rate was 93.7, 37.5, and 66.5% for G1, G3 and G5 respectively, while none ovulations were observed in the other three groups. Alpacas in G1 would produce 25 more ovulations than G3. Results of the present study suggested that the ovulation-inducing factor (OIF) present in seminal plasma is absorbed systemically and that the mechanical action of curettage would contribute to the absorption of the OIF present in seminal plasma.